ASPEK YURIDIS PENGGUNAAN KARTU ATM (ANJUNGAN TUNAI MANDIRI) - Endang Retnowati (Perspektif, 2002)
The launching of ATM (automatic teller machine), as a setl service banking was widely accepted because of its flexible and efficiency. Unfortunately, a so called flexible and efficient service not always offered a fully safety guarantee. The "ATM" appliance sense, customers was often treated as the weak bargaining power party. To increase customer bargaining power, therefore a study to make a regulation that give the protection and guarantee should be immediately conducted.